Sphingosine 1-Phosphate Produced by Sphingosine Kinase 2 Intrinsically Controls Platelet Aggregation In Vitro and In Vivo. Issue 4 (31st July 2015) - Urtz, Nicole; Gaertner, Florian; von Bruehl, Marie-Luise; Chandraratne, Sue; Rahimi, Faridun; Zhang, Lin; Orban, Mathias; Barocke, Verena; Beil, Johannes; Schubert, Irene; Lorenz, Michael; Legate, Kyle R.; et al.
<x xml:space="preserve">Abstract</x> Rationale: Platelets are known to play a crucial role in hemostasis. Sphingosine kinases (Sphk) 1 and 2 catalyze the conversion of sphingosine to the bioactive metabolite sphingosine 1-phosphate (S1P). Although platelets are able to secrete S1P on activation, little is known about a potential intrinsic effect of S1P on platelet function. Objective: To investigate the role of Sphk1- and Sphk2-derived S1P in the regulation of platelet function. Methods and Results: We found a 100-fold reduction in intracellular S1P levels in platelets derived from Sphk2−/− mutants compared with Sphk1−/− or wild-type mice, as analyzed by mass spectrometry. Sphk2−/− platelets also failed to secrete S1P on stimulation. Blood from Sphk2-deficient mice showed decreased aggregation after protease-activated receptor 4-peptide and adenosine diphosphate stimulation in vitro, as assessed by whole blood impedance aggregometry. We revealed that S1P controls platelet aggregation via the sphingosine 1-phosphate receptor 1 through modulation of protease-activated receptor 4-peptide and adenosine diphosphate–induced platelet activation. Finally, we show by intravital microscopy that defective platelet aggregation in Sphk2-deficient mice translates into reduced arterial thrombus stability in vivo. Conclusions: We demonstrate that Sphk2 is the major Sphk isoform responsible for the generation of S1P in platelets and plays a pivotal intrinsic role in the control of platelet activation. Correspondingly, Sphk2-deficient mice are protected from arterial thrombosis after vascular injury, but have normal bleeding times. Targeting this pathway could therefore present a new therapeutic strategy to prevent thrombosis.